Online Learning Media: English Education Department Students’ Perspective - Benni Ichsanda Rahman Hz; Ernita Daulay (Metathesis: Journal of English Language, Literature, and Teaching, 2021)
The use of virtual learning media is now being daily needs since global pandemic appears. All educations units must use virtual platform to ruin learning process. This study is aimed to investigate the effectiveness of virtual media platform used by lecturer from students’ perspective, in teaching and learning process of English education students in Public Speaking subject. Besides, the research focuses on analyzing how effective the media is from students’ point of view. This study is a case study approach, that is natural qualitative. The study involved university students, conducted on one biggest university in Medan, Indonesia, majoring in English Education. The participants were surveyed through questionnaire distributed through Google Survey. The questionnaires and interview were conducted to assemble the data related to students’ experiences in using certain online media given by the lecturers, both provided by the institutions and other platform. By their response, Zoom Cloud Meeting is the most effective media in teaching-learning process, where 79% of them say so. It is followed by Whatsapp, where 41.30% respondents choose it. This findings hopefully will be great consideration for the researcher and other parties, to apply the chosen media in teaching learning process, as students expect in their response.